VAT treatment of the financial services: Implications for the real economy - BAYDUR, Ismail (Institutional Knowledge at Singapore Management University, 2021)
Financial institutions are exempt from the value-added tax (VAT) in most countries. We develop a general equilibrium model with endogenous firm entry and a banking sector to accommodate three key distortions related to exempt treatment: (i) self-supply bias in the banking sector, (ii) under-taxation of payment services, and (iii) input distortions in the business sector and tax cascading. We calibrate our model to the average of Germany, France, and the UK data. Our results show that repealing exempt treatment always increases tax revenues. However, welfare gains occur only at low VAT rates due to the hump-shaped VAT Laffer curve.